Safety of Transrectal or Transvaginal Drainage of Pelvic Abscesses - Mohammed Ilyas, Mohammed Iyoob; Kandagatla, Pridvi; Reickert, Craig A.; Nalamati, Surya; Webb, Shawn P.; Szilagy, Eric J.; Stefanou, Amalia J. (Journal of Coloproctology, 2021)
Objective The literature on the safety and long-term sequelae of transrectal and transvaginal drainage of pelvic abscesses is limited. We evaluated the outcomes and safety of pelvic abscess drainage by interventional radiology at our institution.Methods After obtaining institutional review board approval, we retrospectively evaluated the outcomes of transrectal and transvaginal pelvic abscesses drainage using computed tomography, endorectal ultrasound, and or fluoroscopy.Results The study included 26 patients, with an age range of 24 to 88 years old, out of whom 53.8% were men. A total of 46.1% of the participants were African Americans and 26.9% were Caucasians. The average body mass index was 28.4 (range: 15.6 to 41.9). The most common etiology was penetrating abdominal injury (27%), followed by appendectomy (23%), diverticular disease (11.5%), anastomotic leak (11.5%), and disorders of gynecological causes (11.5%). The mean abscess diameter was 6.3 cm (range: 3.3 to 10.0 cm). Transrectal drainage was performed in all except one patient who had a transvaginal drainage. Transrectal ultrasound was used for drainage in 92.3% cases, and fluoroscopy was used as an additional imaging modality in 75% of the cases. An 8- or 10-Fr pigtail catheter was used in > 80% of the patients. Drains were removed between 2 and 7 days in 92.3% of the cases. The average follow-up was 30.4 months (range: 1 to 107 months), and no long-term complications were reported. Only one patient required subsequent operative intervention for an anastomotic leak.Conclusions Pelvic abscess drainage by transrectal route using radiological guidance is a safe and effective procedure.
Keywords: transrectal; transvaginal; pelvic abscess; interventional drainage